The Influence of Justice, Taxation System, and Discrimination on Individual Taxpayers' Perceptions Regarding Tax Evasion Ethics [Research at the North Malang Pratama Tax Office] - Kahesti, Zulia Tri; Tias Rahmi Fauziyah (Proceeding Economy of Asia International Conference, 2026)
Introduction/Main Objectives: This study examines how fairness, the tax system, and discrimination influence individual taxpayers’ perceptions of the ethics of tax evasion at the North Malang Tax Office (KPP Pratama). Tax evasion remains a persistent issue in Indonesia, often linked to negative perceptions of fairness and systemic weaknesses, making this topic crucial for improving compliance. Background Problems: The research addresses the question: To what extent do fairness, the tax system, and discrimination affect taxpayers’ ethical views on tax evasion? Research Methods: A quantitative approach was employed using purposive sampling to select 100 non-employee individual taxpayers earning above IDR 60 million annually. Data were collected through structured questionnaires and analyzed using multiple linear regression with SPSS version 26.0. Finding/Results: The results indicate that fairness, the tax system, and discrimination significantly and positively influence taxpayers’ perceptions regarding the ethics of tax evasion. The Adjusted R² value of 0.667 suggests that 66.7% of perception changes are explained by these three variables, while the remaining 33.3% is influenced by external factors beyond the study’s scope. Conclusion: The findings underscore the importance of implementing a fair, transparent, and discrimination-free tax system to enhance compliance and reduce tax evasion practices in Indonesia. Policymakers should prioritize equity and clarity in tax regulations to foster ethical taxpayer behavior.